Lateral flow immunoassay for detection of active tuberculosis utilising CFP10-ESAT6 as biomarker - Ariffin, Nazifah (2019)
Tuberculosis (TB) is one of the greatest health care problems in the world. Traditional diagnostic techniques based on the isolation of the tuberculosis bacillus in culture media are time consuming, and it is necessary to wait for several weeks to obtain a result. Therefore, possible biosensor that easy to use and cheap is the lateral flow immunoassay (LFIA), which is affordable, sensitive, specific, and user-friendly. LFIA has been introduced as a handheld immunoassay-based point- of-care platform for an automated detection of TB. The CFP10-ESAT6 antigen of M. tuberculosis were used as the target in early detection of TB using LFIA strip- based point of care strategy